2004
DOI: 10.1016/j.clpt.2003.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Orange juice substantially reduces the bioavailability of the β‐adrenergic–blocking agent celiprolol

Abstract: Orange juice substantially reduces the bioavailability of celiprolol, but the mechanism of this interaction remains to be resolved. For example, modulation of intestinal pH and of function of transporters implicated in the absorption of celiprolol may be involved. Because of the great extent of the orange juice-celiprolol interaction and a wide use of orange juice, this interaction is likely to have clinical importance in some patients, although hemodynamic consequences were not seen in young healthy subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
0
4

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(69 citation statements)
references
References 13 publications
4
61
0
4
Order By: Relevance
“…In contrast to FJ-drug interactions involving CYP3A substrates, decreased bioavailability of OATP2B1 substrates was observed with not only GFJ, but also OJ and AJ (Dresser et al, 2002;Lilja et al, 2004Lilja et al, , 2005Imanaga et al, 2011;Tapaninen et al, 2011;Jeon et al, 2013). Naringin, the main constituent flavonoid of GFJ, is thought to be a major inhibitor of OATP2B1-mediated drug transport in GFJ Shirasaka et al, 2009Shirasaka et al, , 2010aShirasaka et al, , b, 2011aShirasaka et al, , b, 2013 that in GFJ, it is unlikely that naringin is a major contributor to OATP2B1-mediated drug interactions involving OJ and AJ (Ameer et al, 1996;Ho et al, 2000).…”
Section: Introductionmentioning
confidence: 85%
“…In contrast to FJ-drug interactions involving CYP3A substrates, decreased bioavailability of OATP2B1 substrates was observed with not only GFJ, but also OJ and AJ (Dresser et al, 2002;Lilja et al, 2004Lilja et al, , 2005Imanaga et al, 2011;Tapaninen et al, 2011;Jeon et al, 2013). Naringin, the main constituent flavonoid of GFJ, is thought to be a major inhibitor of OATP2B1-mediated drug transport in GFJ Shirasaka et al, 2009Shirasaka et al, , 2010aShirasaka et al, , b, 2011aShirasaka et al, , b, 2013 that in GFJ, it is unlikely that naringin is a major contributor to OATP2B1-mediated drug interactions involving OJ and AJ (Ameer et al, 1996;Ho et al, 2000).…”
Section: Introductionmentioning
confidence: 85%
“…Despite the lack of an effect of cranberry juice on the pharmacokinetics of warfarin (20), several case reports have indicated that cranberry juice results in an enhanced antithrombotic effect of warfarin (8,12,23,27,32,33), suggesting a possible pharmacodynamic effect. A number of studies have reported incidences of apple-, orange-, and grapefruit-drug interactions (6,7,21,29). The potential effect of cranberry juice on drug transporters had not been investigated prior to our study.…”
Section: Discussionmentioning
confidence: 99%
“…It is now known that fruit juices are capable of producing clinically significant drug interactions through the inhibition of carriermediated active transport (6). For example, the levels of absorption of fexofenadine (7), talinolol (29), and celiprolol (21) were markedly reduced by the concurrent ingestion of grapefruit, orange, and apple juices. Although the molecular mechanisms of intestinal transport remain largely unknown, the furanocoumarins and bioflavonoids present in these juices were shown to be potent in vitro inhibitors of organic aniontransporting polypeptides and are suggested to play a role in the observed juice interactions (7).…”
mentioning
confidence: 99%
“…Orange juice contains minor amounts of furanocoumarins and has little CYP3A4 inhibitory effect Won et al, 2010). It has been demonstrated that orange juice reduces the AUC of celiprolol (Lilja et al, 2004), atenolol (Lilja et al, 2005), fexofenadine (Dresser et al, 2002), ciprofloxacin (Neuhofel et al, 2002), and levofloxacin (Wallace et al, 2003). Because at least some of these drugs (e.g., fexofenadine, celiprolol) have been identified as substrates of OATPs expressed in the intestine, uptake inhibition of these transporters may be the cause for these interactions.…”
Section: Drug-food Interactionsmentioning
confidence: 99%